The effects of preferred provider options on use of outpatient mental health services for three employee groups - Wells, Kenneth B., 1948-; Marquis, M. Susan; Hosek, Susan D.; Rand Corporation. Health Sciences Program; United States. Department of Health and Human Services; National Institute of Mental Health (U.S.) (Santa Monica, CA : RAND, 1991)
Preferred provider organizations (PPOs), which offer some of the advantages of both fee-for-service and managed care, are becoming an important market force. This report provides empirical estimates of the effects of offering a PPO option within indemnity plans on use of outpatient mental health services. The data are from a study that examined a sample of employees who had enrolled in indemnity plans before and after a PPO option was offered by three employers in two U.S. sites. The authors found little evidence for either adverse or favorable selection of indemnity enrollees on the basis of their mental health status into use of the PPO option, either for general medical care or for mental health care. After controlling for other factors, the authors found no significant association between mental health status and intent to use PPO providers for general medical care. The pattern of results suggests that established provider relationships, rather than level of mental health status per se, determine selection of provider among users of outpatient mental health care. By the second year following PPO implementation, after controlling for sociodemographic factors and previous use of mental health services, there was no difference in probability of use of outpatient mental health services between employees who expected to use PPO providers and those who did not. But costs per user of mental health services were lower for individuals who relied primarily on PPO rather than non-PPO providers for their mental health care. Thus, despite lower cost sharing for services received from PPO providers, the PPO option appeared to lower outpatient mental health care costs with no more than a transient reduction in access to such care.
Prepared within RAND's Health Sciences Program.
Includes bibliographical references (p. 65-68).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Ambulatory medical care -- Utilization -- United States; Insurance, Mental health; Mental health services -- Utilization -- United States; Preferred provider organizations (Medical care); Ambulatory Care -- utilization -- United States; Health Benefit Plans, Employee -- United States; Mental Health Services -- utilization -- United States; Preferred Provider Organizations -- utilization -- United States